Psalm 58 : a prayer for vengeance - Mare, L. P. (Old Testament Essays, 2003)
Psalm 58 contains an accusation against leaders that they do not execute their duties in righteousness and with fairness. They abused their power, not using it for the benefit of the nation, but for their own personal benefit. The psalmist then prays for the total destruction of these abusers of power, using a series of drastic images. For Christians it is quite disturbing that a person prays for revenge on his enemies in this way. The aim of this article is to show that Psalm 58 not only had a place in the worship life of old Israel, but it also has a place in the worship-life of the Church today.
free